Mean Artery Pressure (MAP) dan Aktivitas Fisik pada Kehamilan : Mean Arterial Pressure (MAP) and Physical Activity in Pregnancy - Sekarini, Ni Nyoman Ayu Desy; Pratiwi, Putu Irma; Sulyastini, Ni Komang; Kurniawati, Yuni; Ida Ayu Kade Trisna Dwiyanti (Indonesian Journal of Midwifery (IJM), 2024)
Hypertension in pregnancy, including preeclampsia and eclampsia, is a leading cause of maternal mortality in Indonesia. This condition can be prevented through early detection, such as routine measurement of Mean Arterial Pressure (MAP) during prenatal check-ups. Daily physical activity, including household chores, is one of the factors that can influence MAP values. This study aimed to analyze the relationship between physical activity and MAP in pregnant women. A quantitative approach with an analytical design and cross-sectional method was employed. The sample consisted of 332 pregnant women in their first, second, and third trimesters who underwent prenatal examinations at 36 independent midwifery practices in Buleleng Regency, selected through Cluster Random Sampling. Primary data were collected on physical activity over one week using the Pregnancy Physical Activity Questionnaire (PPAQ), while MAP was calculated through blood pressure measurements. The analysis using the Chi-square test yielded a p-value of 0.018 (p < 0.05), indicating a significant relationship between physical activity and MAP. The majority of respondents (87.7%) had normal MAP (<90 mmHg), and 88.3% demonstrated good levels of physical activity. Physical activity was shown to play a crucial role in preventing pregnancy-related hypertension. Therefore, pregnant women are encouraged to engage in regular physical activity to reduce the risk of complications during and after pregnancy.    Abstrak Hipertensi dalam kehamilan, termasuk preeklamsia dan eklamsia, merupakan salah satu penyebab utama Angka Kematian Ibu (AKI) di Indonesia. Kondisi ini dapat dicegah melalui deteksi dini, seperti pengukuran Mean Artery Pressure (MAP) secara rutin selama pemeriksaan kehamilan. Aktivitas fisik harian, termasuk kegiatan rumah tangga, menjadi salah satu faktor yang memengaruhi nilai MAP. Penelitian ini bertujuan menganalisis hubungan antara aktivitas fisik dan MAP pada ibu hamil. Penelitian ini menggunakan metode kuantitatif dengan desain analitik dan pendekatan cross-sectional. Sampel terdiri dari 332 ibu hamil trimester I, II, dan III yang melakukan pemeriksaan di 36 Praktek Mandiri Bidan (PMB) di Kabupaten Buleleng, dengan teknik Cluster Random Sampling. Data primer diperoleh dari pengukuran aktivitas fisik selama 1 minggu menggunakan instrumen Pregnancy Physical Activity Questionnaire (PPAQ), serta pengukuran MAP melalui penghitungan tekanan darah. Analisis menggunakan uji Chi-square menunjukkan p-value 0,018 (p < 0,05), yang mengindikasikan adanya hubungan signifikan antara aktivitas fisik dan MAP. Sebagian besar responden (87,7%) memiliki MAP normal (<90 mmHg) dan 88,3% menunjukkan tingkat aktivitas fisik yang baik. Aktivitas fisik terbukti berperan dalam pencegahan hipertensi pada kehamilan, sehingga ibu hamil disarankan untuk tetap melakukan aktivitas fisik secara rutin guna mengurangi risiko komplikasi selama dan setelah kehamilan.